Storm prey - Sandford, John, 1944 Feb. 23- (New York : Berkley Books, 2011)
Weather Karkinnen, surgeon, wife of an investigator named Lucas Davenport, unwittingly witnesses the robbery of the hospital pharmacy where she works. With the death of a pharmacy worker on their hands, the three thieves set out to find out who Weather is, and eliminate the only possible witness ....
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Police -- Minnesota -- Minneapolis -- Fiction; Witnesses -- Minnesota -- Minneapolis -- Fiction; Murder -- Investigation -- Minnesota -- Minneapolis -- Fiction; Minneapolis (Minn.) -- Fiction; Mystery fiction